A Comparative Between British English And American English: Vocabulary Analysis - Novari, Ari Fajria; Maryani, Yeni; Rostiana, Heva (Universitas Mathla'ul Anwar Banten, 2021)
This research paper aims to analyze the comparative between British English and American English, because many language learners or English users still confuse to differentiate both of them, especially in the countries where English is foreign language. Sometimes, it cause misunderstanding in communication. The research paper use qualitative research design with characteristic of content analysis. It uses observation and documentation in collecting the data. The obtained data is vocabulary in Oxford Advanced Learner’s Dictionary 9th edition which published in 2015. The researcher took 150 words to be analyzed. Based on the data analysis there are three differences in Vocabulary of British English and American English. The researchers divide the differences into three categories they are differences in Vocabulary (word using), spelling, and pronunciation. The researcher found 50 different words in vocabulary (word using), 50 different words in spelling and 50 words which have differences in pronunciation. Based on findings of this research, it is significant for language learners or English user to know the differences of British English and American English and improve their vocabulary of British and American English in order to decrease misunderstanding in communication. The researchers hope language learners or English user can decide which English varieties that will they use and the can use one of English varieties consistently.